The Development of Renewable Energies and Supply Security: A Trade-Off Analysis - Luise Röpke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
This paper analyzes the effects of the green transformation on the German electricity sector with respect to the energy political triangle. It focuses on how the development of renewable energies will affect security of electricity supply. In a cost-benefit analysis, the value of supply security is compared with its costs of provision. More specifically, the benefits of maintaining the present quality of electricity supply are the avoided social damages from electricity outages and are compared with the respective investment costs in the low- and medium-voltage distribution grid. It is shown that the transformation process towards a green and decentralized production structure will be costly for society, even though the costs can be reduced by different measures.
Keywords: Q41; Q48; D61; 330; Energy policy; cost-benefit analysis; value of supply security; value of lost load